2017
DOI: 10.1177/0363546517700118
|View full text |Cite
|
Sign up to set email alerts
|

Femoroacetabular Impingement in Professional Football Players: Return to Play and Predictors of Career Length After Hip Arthroscopy

Abstract: Hip arthroscopy for treatment of FAI and associated pathologic abnormalities in professional football players resulted in a high rate of return to play. The study's findings demonstrate that 87% of the arthroscopic procedures allowed professional football players to return to play, linemen were less likely to return compared with other positions, and the presence of microfracture did not significantly affect the return to play rate. These findings support hip arthroscopy as an effective procedure to treat FAI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
80
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 21 publications
2
80
0
1
Order By: Relevance
“…In current study it was found that there is no statistically significant difference in the outcomes within the follow up period of the study between patients who needed debridement of intra-articular cartilage lesions at the time of the arthroscopy and those who didn't have cartilage lesions at the time of the arthroscopy. Menge et al 11 in their study about the return to play in professional footballers following arthroscopic treatment of FAI reported that there is no significant difference in return to play rate between athletes who underwent microfracture and those who did not (25% vs 38%, P = .698). In current study it was found that 3 patients (7.50%) had their arthritis progressed during the follow up with development of radiographic evidence of hip osteoarthritis and failure of non-operative management.…”
Section: Discussionmentioning
confidence: 94%
“…In current study it was found that there is no statistically significant difference in the outcomes within the follow up period of the study between patients who needed debridement of intra-articular cartilage lesions at the time of the arthroscopy and those who didn't have cartilage lesions at the time of the arthroscopy. Menge et al 11 in their study about the return to play in professional footballers following arthroscopic treatment of FAI reported that there is no significant difference in return to play rate between athletes who underwent microfracture and those who did not (25% vs 38%, P = .698). In current study it was found that 3 patients (7.50%) had their arthritis progressed during the follow up with development of radiographic evidence of hip osteoarthritis and failure of non-operative management.…”
Section: Discussionmentioning
confidence: 94%
“…Professional athletes have been shown to return to sport at higher levels than recreational athletes. (32,35) Return to sport appears to be highly influenced by factors such as self-motivation, aging, pain, encouragement, and adaptation to physical limitations. (38,39) These factors as well as monetary incentives and the limited window to play at the elite level motivate professional athletes to return to play.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with existing literature, which supports high return to sport and good performance in professional athletes following hip arthroscopy. [2][3][4][5][6] In The Outliers, Malcolm Gladwell asserts that it takes 10,000 hours of practice to become an expert in any field. 7 Professional athletes possess an unparalleled amount of determination, will, and resilience, which not only place them in the elite few, but also keep them at the highest level year after year.…”
mentioning
confidence: 99%